Genomic prostate score and treatment selection in favourable intermediate‐risk prostate cancer - Eric Margolis; Benjamin H. Lowentritt; Christopher M. Pieczonka; John P. Bennett; Marina Pavlova; Joao Paulo Zambon; Jack Groskopf; Edward Uchio (BJUI Compass)
Abstract Objective To assess the factors associated with the use of active surveillance (AS) in NCCN favourable intermediate‐risk (FIR) prostate cancer (PCa) patients who received the 17‐gene Genomic Prostate Score (GPS) assay. Material and Methods Contemporary data were collected from academic and large community group practices across the United States. Eligible patients had localized PCa classified as FIR per NCCN guidelines and received a GPS report between May 2017 and April 2019. Higher GPS results (scale: 0–100) were associated with a higher risk of adverse outcomes. The proportion of patients selecting AS was calculated with 95% confidence intervals. Uni‐and multivariable logistic regression analyses were performed to determine the association between AS selection and relevant covariates. Results There were 324 eligible patients (Gleason Score 3 + 4, 79%; PSA 10–20 ng/ml, 19%; clinical stage T2b‐T2c, 2%; median percent positive cores, 16.7%; median GPS result, 26). The distribution of GPS results was 0–19 (23%), 20–40 (60%), and 41–100 (16%). Overall, 31% (95% CI 26%, 36%) selected AS: 58% (46%, 69%) with GPS 0–19, 27% (21%, 33%) with GPS 20–40, and 6% (1%, 16%) with GPS 41–100. In univariable models, the Gleason score, percent positive cores, PSA, and GPS results were significantly associated with AS selection. In a multivariable model, the percent positive cores and the GPS result remained significantly associated with AS selection. AS persistence was 91% (82%, 95%) at 12 months. Conclusions The GPS result and percent positive cores appear associated with AS use after controlling for relevant clinical variables in NCCN FIR prostate cancer patients.